Evaluating Strategic Alignment in Syrian Grain Company Field Study on Branch of Latakia - لمى فيصل اسبر (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aims at highlighting the concept Strategic Alignment, and its dimensions, because of its importance in organizations life to achieve strategic success. The research was conducted in Syrian Grain company branch of Latakia, on a purposive sample of managers in all administrative levels, 53 questionnaires were completely answered and analyzed using SPSS23 software, descriptive analysis and statistical inference were used to reach the results that show that the company achieves strategic alignment, implements its strategies and strategic operations, but it has not announced its strategic plan to all its members, therefore the vision and mission are unknown to all employees, which makes some obstacles. The study recommended the necessity of publishing the company's strategic plan and inform employees, and try to find cultural integration among the merged companies that helps achieve the strategic Alignment of the company. Empowering workers and involving them in work and decision-making, which helps to implement the flow of strategic operations. The necessity of having contingency plans to confront the uncertainty to achieve a dynamic strategic alignment.